In Gefahr und größter Not bringt der Mittelweg den Tod - Kluge, Alexander (Germany, 1974)
Frankfurt, 1974. It's carnival time. A female prostitute and thief makes her way through the city with a female GDR spy. At the same time police forcibly evict students from occupied buildings.
The film is contained with other pieces by Alexander Kluge: Porträt einer Bewährung 1964, (12 min.), Biermann-Film 1974, (3 min.), Die Frau auf dem Schlachtfeld 2006, (1 min.), Der starke Ferdinand 1976, (91 min.), Ich war Hitlers Bodyguard 1999, (45 min.), La Habanera 2006, (1 min.).
Options for the subtitles: French, English, Spanish, Russian, Chinese.